Wybrane zagadnienia klasyfikacji obiektów z wykorzystaniem programu komputerowego clusterSim dla środowiska R - Walesiak, Marek (The Selected Problems in Cluster Analysis with Application of Clustersim Computer Program and R Environment, 2007)
Package clusterSim has been written in R language. It contains one main function cluster. Sim and sixteen auxiliary functions. The article presents selected auxiliary functions of clusterSim program and examples of the syntax (procedures) for solving different clustering problems using among others clusterSim package including especially dist.GDM function. These procedures help to resolve a broad range of classification problems that are not available in statistical packages (e.g. SPSS, Statistica, S-Plus, SAS).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 46-56